Estimating global artisanal fishing fleet responses in an era of rapid climate and economic change - Tidd, Alex N.; Caballero, Vasquez; Ojea, Elena; Watson, Reg A.; García Molinos, Jorge (Frontiers in Marine Science, 2023)
There is an urgent need to assess the extent to which the global fishing enterprise can be sustainable in the face of climate change. Artisanal fishing plays a crucial role in sustaining livelihoods and meeting food security demands in coastal countries. Yet, the ability of the artisanal sector to do so not only depends on the economic efficiency of the fleets, but also on the changing productivity and distribution of target species under rapid climate change in the oceans. These impacts are already leading to sudden declines, long-term collapses in production, or increases in the price of fish products, which can further exacerbate excess levels of fishing capacity. We examined historical changes (1950-2014) in technical efficiency within the global artisanal fishing fleets in relation to sea surface temperature anomalies, market prices by taxonomic group, and fuel costs. We show that temperature anomalies affected countries differently; while some have enhanced production from an increase in the resource distribution, which alter the structure of the ecosystem, others have had to adapt to the negative impacts of seawater warming. In addition, efficiency decreases are also related to rises in global marine fish price, whereby more labour and capital are attracted into the fishery, which in turn can lead to an excess in fleet capacity. Our results contribute to the understanding of how the effects of climate-induced change in the oceans could potentially affect the efficiency of artisanal fishing fleets.